Changes in Left Ventricular Global Longitudinal Strain in Patients With Heart Failure and Secondary Mitral Regurgitation: The COAPT Trial - Pio SM; Medvedofsky D; Stassen J; Delgado V; Namazi F; Weissman NJ; Grayburn P; Kar S; Lim DS; Zhou Z; Alu MC; Redfors B; et al. (United States, 2025)
Background
Left ventricular (LV) global longitudinal strain (GLS) provides incremental prognostic information over LV ejection fraction in patients with heart failure (HF) and secondary mitral regurgitation. We examined the prognostic impact of LV GLS improvement in this population.
Methods and Results
The COAPT (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients With Functional Mitral Regurgitation) trial randomized symptomatic patients with HF with severe (3+/4+) mitral regurgitation to transcatheter edge-to-edge repair with the MitraClip device plus maximally tolerated guideline-directed medical therapy (GDMT) versus GDMT alone. LV GLS was measured at baseline and 6-month follow-up. The relationship between the improvement in LV GLS from baseline to 6 months and the composite of all-cause death or HF hospitalization between 6- and 24-month follow-up were assessed. Among 383 patients, 174 (45.4%) had improved LV GLS at 6-month follow-up (83/195 [42.6%] with transcatheter edge-to-edge repair+GDMT and 91/188 [48.4%] with GDMT alone; P=0.25). Improvement in LV GLS was strongly associated with reduced death or HF hospitalization between 6 and 24 months (P<0.009), with similar risk reduction in both treatment arms (Pinteraction=0.40). By multivariable analysis, LV GLS improvement at 6 months was independently associated with a lower risk of death or HF hospitalization (hazard ratio [HR], 0.55 [95% CI, 0.36-0.83]; P=0.009), death (HR, 0.48 [95% CI, 0.29-0.81]; P=0.006), and HF hospitalization (HR, 0.50 [95% CI, 0.31-0.81]; P=0.005) between 6 and 24 months.
Conclusions
Among patients with HF and severe mitral regurgitation in the COAPT trial, improvement in LV GLS at 6-month follow-up was associated with improved outcomes after both transcatheter edge-to-edge repair and GDMT alone between 6 and 24 months.
Registration
URL: https://www.clinicaltrials.gov; Unique identifier: NCT01626079.